2016
DOI: 10.1186/s12960-016-0151-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing motivation and job satisfaction among supervisors of community health workers in marginalized communities in South Africa

Abstract: BackgroundManagement and supervision of community health workers are factors that are critical to the success of community health worker programmes. Yet few studies have explored the perspectives of supervisors in these programmes. This study explored factors influencing motivations of supervisors in community health worker programmes.MethodsWe conducted qualitative interviews with 26 programme staff providing supervision to community health workers in eight community-based organizations in marginalized commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
0
3

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 31 publications
8
56
0
3
Order By: Relevance
“…22 A study by Akintola and Chikoko in Durban found that promotion to supervisory position was cited as one of the factors that motivated CHWs who started as unpaid volunteers and acquired experience on the job. 23 The sex of CHWs has been shown to 24 However, a study by Razee et al (2012) in Papua New Guinea reported that a perceived lack of safety among female CHWs affected motivation to work and resulted in some resigning. 25 In this study, the majority (93%) of CHWs had received training; 76.3% perceived that the training was adequate and 85.8% were confident in performing their duties.…”
Section: Discussionmentioning
confidence: 99%
“…22 A study by Akintola and Chikoko in Durban found that promotion to supervisory position was cited as one of the factors that motivated CHWs who started as unpaid volunteers and acquired experience on the job. 23 The sex of CHWs has been shown to 24 However, a study by Razee et al (2012) in Papua New Guinea reported that a perceived lack of safety among female CHWs affected motivation to work and resulted in some resigning. 25 In this study, the majority (93%) of CHWs had received training; 76.3% perceived that the training was adequate and 85.8% were confident in performing their duties.…”
Section: Discussionmentioning
confidence: 99%
“…While barriers and facilitators to the scale-up and integration of CHWs have been studied in multiple contexts, the perspective of CHWs themselves has not been frequently explored [2024]. …”
Section: Discussionmentioning
confidence: 99%
“…Both the RHWs and the clients reported low engagement in health education programs, due to the less motivation to carry out the health education programs and the few demand needed for health information, respectively. The role of the management system in motivating community health workers has been demonstrated in numerous previous studies [18,19]. The findings of a study conducted in the north of Vietnam among health workers indicated that the motivation of RHWs was influenced by both financial and non-financial incentives, and one of the main motivating factors for them was appreciation by managers, colleagues and the community [20].…”
Section: Discussionmentioning
confidence: 90%